FEATURES OF RAT BLOOD SERUM MARKERS AGAINST THE BACKGROUND OF FLUOROSIS MODELING, ORTHODONTIC INTERVENTION, AND THERAPEUTIC AND PROPHYLACTIC COMPLEX - Shnaider, D.S.; Dienga, A.E.; Rachynskyi, S.V.; Maslov, O.V.; Maslov, V.O.; Tretiak, T.O.; Blazhkiv, N.O. (World of Medicine and Biology, 2025)
The study was devoted to evaluate the influence of a therapeutic-prophylactic complex on blood-serum markers in experimental animals under conditions of modelled fluorosis and orthodontic intervention. Experimental studies were carried out on 40 male Wistar rats (herd breeding), 4 months of age, with an average body mass of 280±14 g. The developed therapeutic-prophylactic complex exhibits pronounced antioxidant and anti-inflammatory (adaptogenic) properties. Its application enhances non-specific resistance under the combined effects of fluoride excess and mechanical stress, as evidenced by normalisation of biochemical markers of oxidative stress and proteolysis. These findings substantiate the feasibility of employing this complex to prevent oxidative damage and inflammatory changes in clinical practice, particularly in orthodontic patients residing in endemic fluorosis areas.